Exploring the Influence of Seller Reputation on Electronic Word of Mouth (e-WOM): Emphasis on Consumer Trust and Satisfaction on E-Commerce Platforms - Ridho Bramulya Ikhsan; Nuraini Sari; Erick Fernando; Juliater Simarmata (Journal of Consumer Sciences, 2025)
Background: The development of e-commerce has been reported to influence consumer behavior in conducting transactions. In this context, direct interaction between buyers and sellers was very limited. Therefore, the seller's reputation was the primary factor used by consumers to assess the credibility and reliability of the e-commerce platform. Purpose: This research aimed to explore the influence of seller reputation on electronic word of mouth (e-WOM) with trust and satisfaction as mediators. Method: An online survey method was adopted, targeting a sample of 300 consumers who had experience transacting on e-commerce platforms in the Greater Jakarta area, and was determined using purposive sampling. Furthermore, the Partial Least Squares-Structural Equation Modeling statistical method provided answers to the research hypothesis. Findings: The results showed that all research hypotheses were accepted. Trust and satisfaction are complementary mediators of the relationship between seller reputation and e-WOM. Conclusions: Based on the results, seller reputation has a positive impact on e-WOM and strengthens the e-commerce ecosystem. Research implication: Sellers who proactively manage consumer reviews increase satisfaction and minimize the impact of negative e-WOM. For e-commerce platforms, implementing a stricter verification system for sellers provided credibility assurance.